2016
DOI: 10.1002/pd.4769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of a positive TORCH and parvovirus B19 screening in pregnancies complicated by polyhydramnios

Abstract: Objective The aim of this study was to evaluate the rate of women with polyhydramnios who eventually screened positive to infectious disease by serum screening testing for TORCH and parvovirus B19.Methods This is a retrospective observational study on singleton pregnancies with a diagnosis of polyhydramnios and who had serum screening for TORCH and parvovirus B19. Patients were followed with serial ultrasounds between 2006 and 2013. Maternal characteristics, medical and obstetric history were reviewed. Ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…Among all patients we found only two cases with infection of Toxoplasma gondii (2.1%). It is similar to the results of the larger study by Pasquini et al [7] who found only 1% of patients with congenital infections and polyhydramnios, including two with Parvovirus B19 and one with Toxoplasma gondii. In both studies congenital infections were found only in patients with mild or moderate polyhydramnios.…”
Section: Discussionsupporting
confidence: 80%
“…Among all patients we found only two cases with infection of Toxoplasma gondii (2.1%). It is similar to the results of the larger study by Pasquini et al [7] who found only 1% of patients with congenital infections and polyhydramnios, including two with Parvovirus B19 and one with Toxoplasma gondii. In both studies congenital infections were found only in patients with mild or moderate polyhydramnios.…”
Section: Discussionsupporting
confidence: 80%
“…Authors of many separate studies on the relationship between intrauterine infections (TORCH, including parvovirosis) and polyhydramnios agree that such correlation is strongly doubtful. Therefore, it seems that in the cases of unexplained polyhydramnios, the diagnosis for TORCH is unjustified [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with the observation of other authors. 9,12,13 There is an association of polyhydramnios with congenital malformation. 9 Six out of 27 patients with mild polyhydramnios (22%) had congenital malformations.…”
Section: Discussionmentioning
confidence: 99%